2002
DOI: 10.1134/1.1466492
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of zirconium-rich seidozerite

Abstract: The crystal structure of seidozerite was refined (a Siemens P4 diffractometer, MoKalpha radiation, It 80 independent reflections, anisotropic refinement, R = 0.053). The monoclinic unit-cell parameters are a = 5.627(1) Å, b = 7.134(1) Å, c = 18.590(4) Å, beta = 102.68(1)°, sp. gr. P2/c, Z = 4. The structural formula, Na1.6Ca0.275Mn0.425Ti0.575Zr0.925[Si2O7]OF, agrees well with the results of the electron probe analysis. Seidozerite is demonstrated to belong to the meroplesiotype polysomatic series including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…The M5 site is occupied by Ti. These results is in good agreement with the cation distribution found in a different specimen of seidozerite by Pushcharovskii et al (2002) except for the M2b position, which in their specimen is dominated by Ca. The variety of cations occupying the M positions in the rosenbuschite group of minerals have quite different ionic radii and valences.…”
Section: Overview Of the Distribution Of Cationssupporting
confidence: 81%
“…The M5 site is occupied by Ti. These results is in good agreement with the cation distribution found in a different specimen of seidozerite by Pushcharovskii et al (2002) except for the M2b position, which in their specimen is dominated by Ca. The variety of cations occupying the M positions in the rosenbuschite group of minerals have quite different ionic radii and valences.…”
Section: Overview Of the Distribution Of Cationssupporting
confidence: 81%
“…Rastsvetaeva et al (1991) stated that the lower symmetry of rinkite from Khibiny is due to the order of REEs and Ca and concluded that their model is in good agreement with all previous work. Christiansen et al (1999) and Christiansen and Rønsbo (2000) analysed the s t r u c t u r a l r e l a t i on be t w e e n g ö t z e n i t e [Ca 2 Ca 2 NaCa 2 Ti(Si 2 O 7 ) 2 OF 3 , space group P1; Table 1] and rinkite and stated that the models of Rastsvetaeva et al (1991) and Galli and Alberti (1971) are the same except for the lower symmetry of the first due to minor ordering of some cations. As noted above, the latest structure refinement of rinkite was done by Sokolova and Cámara (2008a) and is in good agreement with the work of Galli and Alberti (1971).…”
Section: Previous Worksupporting
confidence: 76%
“…= 3.45 g cm À3 , with an approximate formula (Ti,Nb,Al,Zr)(Na,Ca) 3 (Ca,Ce) 4 (Si 2 O 7 ) 2 (O,F) 4 . Rastsvetaeva et al (1991) refined rinkite from the Khibiny massif, Kola Peninsula, Russia: a = 5.679, b = 7.412, c = 18.835 Å , a = 101.26º, V = 777.6 Å 3 , space group P2 1 , Z = 2, D calc. = 3.36 g cm À3 , with the structural formula {TiF (O,F)…”
Section: Previous Workmentioning
confidence: 99%
See 2 more Smart Citations